Foreign and Native-Born STEM Graduates and Innovation Intensity in the United States - John V. Winters (Institute for the Study of Labor (IZA), 2014)
This paper examines the effects of foreign- and native-born STEM graduates and non-STEM graduates on patent intensity in U.S. metropolitan areas. I find that both native and foreign-born STEM graduates significantly increase metropolitan area patent intensity, but college graduates in non-STEM fields have a smaller and statistically insignificant effect on patenting. These findings hold for both cross-sectional OLS and 2SLS regressions. I also use time-differenced 2SLS regressions to estimate the effects of STEM-driven increases in native and foreign college graduate shares and again find that both native and foreign STEM graduates have statistically significant and economically large effects on innovation. Together these results suggest that policies that increase the stocks of both foreign and native STEM graduates increase innovation and provide considerable economic benefits to regions and nations.
Keywords: I25; J24; J61; O31; R12; 330; STEM; innovation; patents; human capital; higher education